(untitled) (Journal of Applied Learning and Teaching, 2024)
Delirium is a neuropsychiatric syndrome that is sudden in onset and represents an acute medical emergency. Nurses must be able to recognise this change in presentation and seek support to assess and treat the underpinning conditions driving delirium. This paper reports a study undertaken at one university in the North-East of England. The study adopted a mixed methods approach to evaluate and explore first-year student nurses’ perceptions and experiences of a blended delirium education package (online and in person). It also explores if students believe this will change or influence their practice. Data were collected via an online questionnaire from 49 students following the completion of an online supported learning package and linked classroom-based simulation. Quantitative data were analysed using descriptive statistics. Qualitative data were thematically analysed using Braun and Clarke’s (2006) thematic analysis principles. Both data strands were integrated to highlight core experiential themes. Two themes were identified: Acknowledging the complexity of delirium and bridging the online-supported learning and classroom teaching and learning activity. This study demonstrated that a blended approach to delirium education is well-received and positively supports student nurses’ understanding of delirium and confidence in practice. Still, there is a need for further refinement in educational practice.